Predictor of joint damage in rheumatoid arthritis - Sumariyono Sumariyono; H Isbagio (Indonesian Rheumatology Association, 2010)
Objective: This study was implemented to determine the joint damage predictor in rheumatoid arthritis (RA).Methods: A cross-sectional study was conducted on outpatients of the rheumatology clinic at Cipto Mangunkusumo General Hospital who had suffered from RA for more than 2 years during the period from October 1, 1999 to June 30, 2000. During this period, we obtained 23 RA patients who fulfi lled the inclusion and exclusion criteria. We evaluated the patients’ medical data that included gender, education, age of onset, rheumatoid factor (RF), C-reactive protein (CRP), and erythrocyte sedimentation rate (ESR). Then we carriedout examinations and tests including X-ray of hand and wrist joints, RF, CRP, and ESR. The degree of joint damage was evaluated using the Larsen score.Results: Twenty three patients—all women, mean age of onset was 36.7 years, mean duration of disease was 62.8 months, educational level with high school degree or above were found in 19 cases (82.6%), and RF (+) at initial treatment were found in 10 cases (43.5%). The mean ESR at initial treatment was 77.9 mm/hr and CRP at initial treatment was between 0 and 768 mg/dL. The Larsen score ranged between 0 and 68 with a meanof 21.7. In bivariate analysis, the Larsen score was signifi cantly higher in the group with positive RF at initial treatment compared to that in the group with negative RF at initial treatment (p = 0.031). C-reactive protein and ESR at initial treatment and the age of onset did not have any signifi cant correlation with the Larsen score, but there was a signifi cant correlation of CRP and ESR during the study with the the Larsen score.Conclusion: RF level was the most signifi cant predictor in determining the degree of joint damage according to the Larsen score while initial positive RF had lower signifi cance level.